Characterization of phytoplankton-excreted metabolites mediating carbon flux through the surface ocean - Yuting Zhu; Hanna S. Anderson; Eli Salcedo; Samuel E. Miller; Krista Longnecker; Melissa C. Kido Soule; Sheean T. Haley; Gretchen J. Swarr; Rogier Braakman; Sonya T. Dyhrman; Elizabeth B. Kujawinski (Proceedings of the National Academy of Sciences, 2026)
The marine labile dissolved organic carbon (DOC) pool is a dynamic reservoir of thousands of molecules that cycles approximately one-quarter of Earth’s primary production within days to weeks. After excretion by phytoplankton and other microbes, metabolites are rapidly consumed, resulting in low standing concentrations (picomolar to low nanomolar). Despite the decades-long search for labile DOC sources and molecular identities, marine phytoplankton exometabolomes are not well characterized, largely due to difficulties in measuring small polar molecules in saline water. Here, we profiled the exometabolomes of six axenic phytoplankton species representing key functional groups including a diatom ( Thalassiosira pseudonana CCMP1335), a picoeukaryote ( Micromonas commoda RCC299), a coccolithophore ( Gephyrocapsa huxleyi CCMP371), a diazotrophic cyanobacterium ( Crocosphaera watsonii WH8501), and two picocyanobacteria ( Prochlorococcus marinus MIT9301 and Synechococcus WH8102). From these cultures, we quantified 56 amine- and alcohol-containing exometabolites representing 11 compound classes which in sum comprised up to 23.4% of phytoplankton-excreted DOC. We estimated that these phytoplankton-derived exometabolites could supply up to 5% of the daily carbon quota of the dominant heterotrophic bacterium SAR11 in the surface ocean. Substantial variations in exometabolite identity and concentration across phytoplankton taxa underscore taxonomic diversity as a key driver in the supply and composition of labile DOC. This taxonomic variation predicts geographic and seasonal differences in the distribution of marine dissolved metabolites that underpin the cycling of labile DOC back to carbon dioxide (CO 2 ). Overall, our work suggests that phytoplankton exometabolites are key chemical currencies that mediate significant carbon fluxes within the ocean’s carbon cycle.